Recent Developments in Arylation of N-Nucleophiles via Chan-Lam Reaction: Updates from 2012 Onwards - Abedinifar, Fahimeh; Mahdavi, Mohammad; Rezaei, Elham b.; Asadi, Mehdi; Larijani, Bagher (Current Organic Synthesis, 2022)
''Chan-Evans-Lam'' (CEL) reaction is the copper-mediated cross-coupling of N-nucleophiles with boronic acids that was independently reported in 1998 by Chan, Evans, and Lam for the first time. This reaction is accomplished at room temperature with a remarkably wide range of nucleophiles. In the recent decade, it has been particularly attractive as a convenient method for constructing the various C– N bonds in organic synthesis. Therefore, a comprehensive survey through all reported process was crucial. In this review, we summarized research progress about N-Arylation, based on the type of N-nucleophile involved in this reaction and catalysts from 2012 onwards.
Keywords: boronic acid